EFEKTIVITAS PEMBERIAN EKSTRAK BUAH BIT (Beta vulgaris) TERHADAP KENAIKAN HEMOGLOBIN (Hb)IBU HAMIL TRIMESTER III DENGAN ANEMIA DI KOTA BENGKULU - Linda Yusanti; Ferna Dwi Mella; Dara Himalaya (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Anemia in pregnancy occurs due to physiological changes during pregnancy. Pregnant women are advised to take Fe tablets during pregnancy, and to support their absorption, they are recommended to consume vitamin C. Beetroot extract contains vitamin C, iron, and zinc. Purpose: This study aims to determine the effectiveness of administering beetroot extract (Beta vulgaris) in increasing hemoglobin (Hb) in third-trimester pregnant women with anemia in Bengkulu City. Methods: The research sample consisted of 20 respondents, with 10 respondents each in the intervention and control groups. The research method used a quasi-experimental design with a two-group pretest-posttest design. Sampling used an accidental sampling technique. Data analysis used the Wilcoxon test and paired sample t-test. Before the intervention was given, the average Hb level was 9,6 gr/dL, and after beetroot extract was administered, the average Hb level increased to 10,3 gr/dL. The average difference between the two groups was 0,82. Results: The results of the bivariate analysis showed that the p-value = 0.041 < α = 0.05, so it can be concluded that administering beetroot extract (Beta vulgaris) is more effective than the control group in increasing hemoglobin (Hb) in third-trimester pregnant women in Bengkulu City. Conslusion: Therefore, it can be an option for pregnant women in preventing and treating anemia.